Ecscw 2009 2009
DOI: 10.1007/978-1-84882-854-4_3
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Nurses' Information Flow by Integrating Paper and Digital Charting

Abstract: Abstract. Information technology has changed the way health care is delivered. Electronic health records which are prevalently deployed to replace or supplement paper documentations have made distributed information access at various points of care and work activity achievable with the use of mobile information devices. Our particular concern is with nurse's information flow, where nurse's notes and observations taken at the point of care feed into the electronic record. In these cases, digital technology has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Research has shown that information flow analysis is an effective method used for understanding user perspectives toward needs regarding HIT design and implementation. [8][9][10][11][12][13][14] In the evidence to date, LTC HIT has both positive and negative effects on nursing practice and care quality. 5,6,12,[15][16][17] The careful consideration of the needs of nursing practice specific to the LTC setting was important and is addressed by the majority of the studies.…”
Section: Background and Significancementioning
confidence: 99%
“…Research has shown that information flow analysis is an effective method used for understanding user perspectives toward needs regarding HIT design and implementation. [8][9][10][11][12][13][14] In the evidence to date, LTC HIT has both positive and negative effects on nursing practice and care quality. 5,6,12,[15][16][17] The careful consideration of the needs of nursing practice specific to the LTC setting was important and is addressed by the majority of the studies.…”
Section: Background and Significancementioning
confidence: 99%
“…Based on their longitudinal field studies in a hospital, including the computerson-wheels study previously described, Tang and Carpendale (2009b) developed a prototype technology that made use of digital pen and paper that allowed nurses to continue to use their familiar pen and paper to create their paper notes. The handwritten notes could be easily transformed into digital texts for documentation without navigating the hierarchical EHR system.…”
Section: Technology For Supporting Information Accessmentioning
confidence: 99%
“…We will focus our future work toward the use of numeric pens [9] to allow carers to create and manage a virtual boundary between the numeric informational system and the local ambient informational ecology. This boundary could be easily set up through turning on/off the device while writing.…”
Section: The Point: Design Of An Integrative Mockupmentioning
confidence: 99%